Sleep and Polysomnographic Disorders in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Polysomnographic findings in 90 children with headaches and complaints of sleep problems were correlated with type of headache (migraine in 60, chronic migraine in 11, tension headache (6), and nonspecific headache (13)), headache severity, body mass index, and medical treatment, in a study at St Christopher's Hospital for Children, Philadelphia, PA.